Dinamika Hukum Lingkungan Didalam Konsep Pelaksanaan Berkelanjutan Di Indonesia - Ihsanudin Herry Setyawan; Muhammad Evan Kurnia; Rayi Kharisma Rajib (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
This research article has the title "Dynamics of Environmental Law in the Concept of Development and Implementation of Sustainable Development in Indonesia." The research method used in writing this article is a qualitative method with a normative juridical approach. The data that will be used is relevant data from a book, scientific article, news or other written sources. The sources of data collection are related to the titles studied, both from primary legal materials and secondary legal materials. This research aims to find out the concept of sustainable development, how to realize sustainable development goals and implement environmental law enforcement. The results of this research are that people tend to carry out activities that are detrimental to the environment to fulfill their interests. Therefore, it is necessary to take into account the impact of any sustainable development on the environment. In order for the implementation of sustainable development to be achieved, all development needs to have environmental permits and enforce environmental laws.